Estudos sobre mutação em Trypanosoma cruzi: desenvolvimento de uma nova abordagem metodológica e efeitos do Cádmio - Carolina Furtado Torres da Silva (2005)
The protozoan Trypanosoma cruzi is the etiologic agent of Chagas disease, a chronic ilness afflicting over 18 million people in Americas (WHO, 2002). Different studies including biological, biochemical and molecular ones have demonstrated that T. cruzi is a very heterogeneous taxon (Macedo et al, 2004). However, it has been proposed that T. cruzi has a clonal population structure in which sexual reproduction is rare or absent (Ayala, 1993). Therefore, we asked how T. cruzi achieves this remarkable heterogeneity among the strains and clones. One could then expect that DNA repair would play a role since the function of mismatch repair (MMR) in decreasing the mutation rate is well understood (Hsieh, 2001). It has been proposed that different T. cruzi strains have different mismatch repair ability under stress conditions and consequently different mutations rates (Augusto-Pinto et al, 2003). In this work, we have carried out studies about mutation in three T. cruzi strains by evaluation of the role of cadmium in causing genomic instability in T. cruzi and investigation of possible differences in mutation rates among strains. Here, we described the development of a new methodology, based on strains carring a mutant gfp allele which codes for an inactive GFP protein, through wich it will be possible to directly determine the mutation rate in T. cruzi through FACS analysis of the fluorescence emitted by cells transfected with gfp. Using the transfected strains, the results indicate that cadmium, in the presence of hydrogen peroxide, induces an increase in mutation rate of the CL Brener and Colombiana strains. We also verified that cadmium inhibits ATP hydrolysis by recombinant TcMSH2 protein. Finally, we investigated the genomic stability of the JG, CL Brener and Colombiana strains treated with cadmium and hydrogen peroxide for different period of time (30 to 60 days) through analysis of two markers of Trypanosoma cruzi variability: microsatellite instability and sequences wich code to antigenic proteins. It was not possible to observe mutations on the used markers, under the treatment conditions, in contrast to the results obtained with the gfp transfected strains.